Two Decades of KPI Research: A Bibliometric Mapping and Trend Analysis - Nor Asiah Taib; Izlawanie Muhammad; Suhaila Abdul Hamid (Global Academic Excellence (M) Sdn Bhd, 2026)
Tier 3- Indexed by MyCite